Efficient removal of hexavalent chromium (Cr(VI)) from wastewater using FeCl3-modified Chlorella-based biochar - Moon, Soeun; Lee, Chang Gu; Shin, Gwy Am; Park, Seong Jik (Korean Journal of Chemical Engineering, 2023)
This study focuses on the adsorption of hexavalent chromium (Cr(VI)), a harmful heavy metal, using two types of chlorella-based biochar (biochar pyrolyzed at 200 °C (CB200) and iron chloride (FeCl3)-modified biochar pyrolyzed at 200 °C (FeCB200)), and the testing of their effectiveness for the removal of Cr(VI). The FeCB200 sample exhibited the highest removal efficiency (1 g L−1=66.12±1.01%; 5 g L−1=98.48±0.22%) compared to raw biomass (1 g L−1=54.05±0.00%; 5 g L−1=90.09±0.26%) and CB200 (1 g L−1=51.80±0.78%; 5 g L−1=94.74±0.26%) in 100 mg L−1 Cr(VI) solution. The adsorbents were characterized using various characterization techniques, and adsorption experiments were carried out using varying doses of the adsorbent (1 and 5 g L−1). Pseudo-second-order model provided the best fit for the adsorption kinetics, and Redlich-Peterson model exhibited good fitting for the adsorption isotherm (R2>0.972), although variations were observed depending on the dose. Further, the applicability of FeCB200 was assessed using real wastewater spiked with Cr(VI). Although the presence of organic matter resulted in a reduction in the adsorption effectiveness of FeCB200, the difference was not significant (1 g L−1=54.27±3.19%; 5 g L−1=98.48±0.22%). These results demonstrate the promising potential of FeCl3-modified chlorella-based biochar as a valuable adsorbent for the Cr(VI) removal from water environments.
Keywords: Adsorption; Biochar; Chlorella; Cr(VI); FeCl3 Modification